Depression and anxiety among pregnant women during COVID 19 pandemic in Ethiopia: a systematic review and meta-analysis - Gebeyehu Wondmeneh, Temesgen; Wogris, Mohhamed (Frontiers in Global Women's Health, 2024)
BackgroundCoronavirus Disease-19 pandemic had an adverse impact on the mental health of the public worldwide, but the problem is worst among pregnant women due to social distancing policies and mandatory lockdown, including prenatal care services. As a result, the prevalence of depression and anxiety could increase during the pandemic, particularly among pregnant women. Thus, the purpose of this review is to determine the magnitude of depression and anxiety and contributing factors among pregnant women during the pandemic in Ethiopia.MethodsWeb of Science, Since Direct, PubMed, Google Scholar, and African Journals Online were the electronic databases searched, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines were followed in this review. The Newcastle-Ottawa Critical Appraisal Checklist was used to assess the quality of the included studies. A predefined data extraction sheet developed in Excel was used to extract the data. The pooled prevalence of anxiety and depression was determined by a random effect model meta-analysis.Results4,269 and 1,672 pregnant women were involved in depression and anxiety studies, respectively. The pooled prevalence of depression and anxiety among pregnant women during the COVID-19 pandemic in Ethiopia was 24.7% (95% CI: 18.52–30.87) and 35.19% (95% CI: 26.83–43.55), respectively. Single marital status (AOR = 2.22, 95% CI: 1.07–3.37), poor social support (AOR = 2.7, 95% CI: 1.06–4.35), unplanned pregnancies (AOR = 2.17, 95% CI: 1.34–3.0), and unsatisfied marital status (AOR = 2.16, 95% CI: 1.17–3.14) were risk factors for depression. Violence against intimate partners (AOR = 2.87, 95% CI: 1.97–3.77) and poor social support (AOR = 1.98, 95% CI: 1.24–2.71) were risk factors for anxiety.ConclusionOne-fourth and nearly one-third of pregnant women had depression and anxiety, respectively, during COVID-19 pandemic in Ethiopia. Single or unsatisfied marital status and unplanned pregnancies were risk factors for depression. Poor social support was significantly associated with depression and anxiety. Pregnant women who experienced violence against intimate partners had higher anxiety. After COVID-19 pandemic, mental health interventions are essential for reducing depression and anxiety.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=527148, PROSPERO (CRD42024527148).